2008
DOI: 10.1108/10662240810883335
|View full text |Cite
|
Sign up to set email alerts
|

Customer satisfaction factors of mobile commerce in Korea

Abstract: Purpose -The purpose of the paper is to distinguish features of m-commerce from those of e-commerce and identify factors to influence customer satisfaction (m-satisfaction) and loyalty (m-loyalty) in m-commerce by empirically-based case study. Design/methodology/approach -First, based on previous literature, the paper builds sets of customer satisfaction factors for both e-commerce and m-commerce. Second, features of m-commerce are identified by comparing it with current e-commerce through decision tree (DT). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(155 citation statements)
references
References 20 publications
(30 reference statements)
8
137
0
10
Order By: Relevance
“…There are valid measures for attitudes and intentions in both online and mobile advertising [39], [13], [1], [11]. The questions regarding mobile game specificfactors and features of incentive systems were self-formulated basis on the earlier research [39], [38] and [12] as well as the interview data.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…There are valid measures for attitudes and intentions in both online and mobile advertising [39], [13], [1], [11]. The questions regarding mobile game specificfactors and features of incentive systems were self-formulated basis on the earlier research [39], [38] and [12] as well as the interview data.…”
Section: Methodsmentioning
confidence: 99%
“…It is an assessment of one's beliefs regarding the consequences arising from a behavior [14]. This model has been used quite widely in previous studies to explain the advertising effectiveness for other formats [39], [13], [1], [11]. …”
Section: Research Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Clarke (2001) proposed that effective satisfaction must be able to create loyalty amongst customers. Previous studies have demonstrated that customer satisfaction positively affects customer loyalty (Cho et al, 2008) or negatively affects switching intention (Walsh et al, 2006).…”
Section: Customer Satisfaction and Loyaltymentioning
confidence: 99%